Shaping cardiac destiny: the role of post-translational modifications on endoplasmic reticulum – mitochondria crosstalk in cardiac remodeling - Zhang, Xiaohan; Shi, Shuqing; Du, Yihang; Chai, Ruoning; Guo, Zezhen; Duan, Chenglin; Wang, Huan; Hu, Yuanhui; Chang, Xing; Du, Bai (Frontiers in Pharmacology, 2024)
Cardiac remodeling is a shared pathological change in most cardiovascular diseases. encompassing both adaptive physiological responses and decompensated pathological changes. Anatomically, atrial remodeling is primarily caused by atrial fibrillation, whereas ventricular remodeling is typically induced by myocardial infarction, hypertension, or cardiomyopathy. Mitochondria, the powerhouse of cardiomyocytes, collaborate with other organelles such as the endoplasmic reticulum to control a variety of pathophysiological processes such as calcium signaling, lipid transfer, mitochondrial dynamics, biogenesis, and mitophagy. This mechanism is proven to be essential for cardiac remodeling. Post-translational modifications can regulate intracellular signaling pathways, gene expression, and cellular stress responses in cardiac cells by modulating protein function, stability, and interactions, consequently shaping the myocardial response to injury and stress. These modifications, in particular phosphorylation, acetylation, and ubiquitination, are essential for the regulation of the complex molecular pathways that underlie cardiac remodeling. This review provides a comprehensive overview of the crosstalk between the endoplasmic reticulum and mitochondria during cardiac remodeling, focusing on the regulatory effects of various post-translational modifications on these interactions.